Determinación de la calidad del agua para uso doméstico de la quebrada Rumiyacu, en el área de conservación municipal Rumiyacu – Mishquiyauc, Moyobamba - Azabache Liza, Yrwin Francisco (2012)
Water pollution is one of the most slgnificant problems in modern cities and the main pollutant is the people themselves through domestic and agricultura! waste. In the Municipal Conservation Area Rumiyacu - Mishquiyacu, located in the high jungle San Martín region in Peru, does not escape that reality. This thesis was entitled "DETERMINING THE QUALITY OF WATER FOR DOMESTIC USE OF THE RUMIY ACU BROKEN IN MISHQUIY ACU RUMIY ACU CONSERVATION AREA MUNICIPAL-." The focus of research is to monitor the physical parameters, chemical and bacteriological and then a comparison of results with reference values recommended by the legal regulations of the Environmental Quality Standards for drinking water according to the category A-1 which are those waters that are drinkable with disinfection. The work was performed in the Microbasin -Rumiyacu - Misquiyaquillo Moyobamba district, Moyobamba province and San Martín department. 04 stations were determined. Station 1 (E-1): Micro-Header, Station 2 (E-2): Middle part of the watershed, Station 3 (E-3): Entrance to the water treatment plant of the EPSMoyobamba, Station 4 (E-4): Rumiyacu Creek Mouth. The water quality was conducted through 4 months of samples at intervals of one month which all samples were taken to the company providing the services (EPS-Moyobamba). Field was analyzed physical and chemical parameters, total coliforms, fecal coliforms, turbidity, pH, Conductivity, Total Dissolved Solids, Color, Total Hardness, Chloride, Sulfate, Nitrate, Iron, Manganese, Sodium, Copper, Zinc, and Arsenic. The Seasons (E): E 01, E 02, E 03, E 04, analyzed, are found within the physical, chemical and bacteriological standards by category are: Category 01: population and recreation, in reference to the Water Resources Act DL 29338. Classification according to the use. The Micro-Rumiyacu- Misquiyacu is considered protective zone found in the Municipal Conservation Area (MCA), so it intends to implement measures to conserve the environmental quality of this water resource as well as establish ongoing surveillance measures in the area to prevent human population settlement that deteriorate environmental quality of the water. Key words: protective zone, environmental quality.